Time Limit Based Wireless Network Design Using Linux Ubuntu Server 20.04 - Ardana, Febi; Kanedi, Indra; Prasetyo, Eko (Jurnal Komputer Indonesia, 2023)
One system that can manage and limit time on a network uses a time limit system. Linux Ubuntu Server 20.04 is an open source operating system, this operating system is very good for use as a server because it does not require high hardware specifications and can also be obtained for free because it is open source. The network system using time line is very well implemented at the Hidayatullah Foundation, Bengkulu City, this is because at the Hidayatullah Foundation, Bengkulu City, the computer network in the computer and visual laboratory is used by the students, both for learning and teaching activities as well as the media used by the students to fill their time. free. In limiting time using this system is very good.